Pola Internalisasi Identitas Kebangsaan Ormas-Ormas di Kota Medan - MUBA SIMANIHURUK; HUSNUL ISA HARAHAP; SRI ALEM BR. SEMBIRING (Politeia: Jurnal Ilmu Politik, 2014)
This is a study about national identity. National identity is sense of belonging to the state. The focus is to describe iInternalization patterns the national identity of non government religious organization in Medan City. The finding of this study is there are non-standard pattern the internalization national identities of non government religious organization in Medan City. There is only routine activities such as socialization conducted by government agencies such as kesbanglinmaspol. Other institutions such as the Forum for Religious Harmony (FKUB) activity is focused on the establishment of houses of worship socialization. This study is using political identity approach. Data collection is using field study techniques and literature (method inter-views, library research (library research) and study documents. Analysis is using qualitative technique, especially descriptive analysis method.Keywords: National identity, nationalism, non government religious organization.